Über die Konstruktion einer hierarchischen Textverbundgesamtstruktur. Ein Beitrag zur Theorie der Wörterbuchform - Herbert Ernst Wiegand (Lexikos, 2016)
On the Construction of a Hierarchical Comprehensive Text Compound Structure. A Contribution to the Theory of Dictionary Structures. After a brief critical look at research on comprehensive text compound structures in the period 1988 to 2016 an excerpt of a typology of types of text compounds and hierarchical text compound structures is presented and commented on. Following a terminological discussion, especially regarding the concept of lexicographic constituents, a hierarchical comprehensive text compound structure with right expanded text compound structure is constructed as an example step by step, in such a way that its partial structures, i.e. the hierarchical right expanded text compound constituent structure, its hierarchical constituentless front and back matter structure, its hierarchical word list structure and its hierarchical article stretch structures, are constructed separately and are then combined. In this process a number of new concepts are coined and relevant terms are introduced, e.g. front and back matter sector, hybrid front and back matter constituents, front front matter and back back matter. In addition, because dictionaries and utility objects with lexicographical structural features always display at least one outer access structure, it is considered if and how at least outer alphabetical main access structures can be considered in the construction of hierarchical comprehensive text compound structures. In conclusion a proposal is made in this regard.